ANALISIS DAYA DUKUNG PROMOSI EKOWISATA KELURAHAN SITU GEDE KECAMATAN BOGOR BARAT KOTA BOGOR - Prameswari Handayani; Dipo Krishyudi Ono; Sabila Adinda Puri Andarini (UNIVERSITAS PAKUAN, 2023)
The tourism carrying capacity is the ability of a tourist attraction to accommodate tourists at a certain area and time, which is supported by the socioeconomic, sociocultural, and biogeophysical of a location without reducing the quality of the environment and tourist satisfaction in enjoying the attraction. The purpose of this study is to analyze the carrying capacity of ecotourism promotion, Situ Gede Village, West Bogor District, Bogor. This research is conducted with qualitative research methods. This research adopts the tradition of qualitative research case studies about the supporting capacity of Situ Gede ecotourism promotion which is carried out on weekdays, to be able to find out the ongoing process of activities so that we can meet with residents and visitors who are working on ecotourism promotion activities and KOMPEPAR members who are on duty. The results showed that the promotion of Situ Gede ecotourism through social media has not been effective because the informants we have interviewed said that management and legality have not been effective, therefore social media has not been effective as a promotional media to professionally increase the economic condition of Situ Gede, West Bogor District, Bogor. More efforts are still needed to optimize the promotional activities on Situ Gede ecotourism social media.